Measuring core inflation in India: An asymmetric trimmed mean approach - Naresh Kumar Sharma; Motilal Bicchal (Cogent Economics & Finance, 2015)
The paper seeks to obtain an optimal asymmetric trimmed mean-based core inflation measure in the class of trimmed mean measures when the distribution of price changes is leptokurtic and skewed to the right for any given period. Several estimators based on asymmetric trimmed mean approach are constructed and estimates generated by use of these estimators are evaluated on the basis of certain established empirical criteria. The paper also provides the method of trimmed mean expression "in terms of percentile score." This study uses 69 monthly price indices which are constituent components of Wholesale Price Index for the period, April 1994 to April 2009, with 1993 - 1994 as the base year. Results of the study indicate that an optimally trimmed estimator is found when we trim 29.5% from the left-hand tail and 20.5% from the right-hand tail of the distribution of price changes.
Keywords: 330; core inflation; inflation; asymmetric trimmed mean; Wholesale Price Index